Concept Analysis of Transition from Nursing Studentship to Working Life: a Hybrid Model - Forough Rafii; Mahbobeh Sajadi Hezaveh; Naiemeh Naiemeh Seyedfatemi (Tehran University of Medical Sciences, 2014)
Background & Aim: Transition from studentship to working life is a stressful and challenging event. The concept of transition is important in nursing education, management, and practice issues. However, despite its supreme importance, there are certain ambiguities about the concept of transition in nursing. The aim of this study was to analyze the concept of transition in the context of nursing in Iran.   Methods & Materials: We used the three-phase hybrid concept analysis model including the theoretical phase, the fieldwork phase, and the final analytic phase in this study. In the theoretical phase, we conducted an online literature search to find relevant articles published prior to 2012. In the fieldwork phase, five novice nurses, two experienced nurses, and one head-nurse were interviewed. Interviews were transcribed verbatim and analyzed using thematic analysis approach. During the final analytic phase, we compared the findings of the first two phases to provide a clear and comprehensive definition of the concept of transition .   Results: The findings of the theoretical phase revealed that transition was a process phenomenon having defined attributes such as detachment, individual perception, awareness, and human response patterns. According to the findings of the fieldwork phase, transition was an interactive, evolutionary, and time-bound phenomenon that embodies attributes such as socialization, unavoidability, and competence and ability development. In the final analytic phase, a comprehensive definition was provided for the concept of transition in the context of nursing in Iran .   Conclusion: This study provided a comprehensive understanding of the concept of transition from nursing studentship to working life in Iran. The findings of this study can be used to develop theories, instruments, and criteria for evaluation of novice nurses' transition to experienced nurses .